Substrate Specificity, Membrane Topology, and Activity Regulation of Human Alkaline Ceramidase 2 (ACER2) - Sun, Wei (American Society for Biochemistry and Molecular Biology, 2010)
Human alkaline ceramidase 2 (ACER2) plays an important role in cellular responses by regulating the hydrolysis of ceramides in cells. Here we report its biochemical characterization, membrane topology, and activity regulation. Recombinant ACER2 was expressed in yeast mutant cells (Δypc1Δydc1) that lack endogenous ceramidase activity, and microsomes from ACER2-expressiong yeast cells were used to biochemically characterize ACER2. ACER2 catalyzed the hydrolysis of various ceramides and followed Michaelis-Menten kinetics. ACER2 required Ca(2+) for both its in vitro and cellular activities. ACER2 has 7 putative transmembrane domains, and its amino (N) and carboxyl (C) termini were found to be oriented in the lumen of the Golgi complex and cytosol, respectively. ACER2 mutant (ACER2ΔN36) lacking the N-terminal tail (the first 36 amino acid residues) exhibited undetectable activity and was mislocalized to the endoplasmic reticulum, suggesting that the N-terminal tail is necessary for both ACER2 activity and Golgi localization. ACER2 mutant (ACER2ΔN13) lacking the first 13 residues was also mislocalized to the endoplasmic reticulum although it retained ceramidase activity. Overexpression of ACER2, ACER2ΔN13, but not ACER2ΔN36 increased the release of sphingosine 1-phosphate from cells, suggesting that its mislocalization does not affect the ability of ACER2 to regulate sphingosine 1-phosphate secretion. However, overexpression of ACER2 but not ACER2ΔN13 or ACER2ΔN36 inhibited the glycosylation of integrin β1 subunit and Lamp1, suggesting that its mistargeting abolishes the ability of ACER2 to regulation protein glycosylation. These data suggest that ACER2 has broad substrate specificity and requires Ca(2+) for its activity and that ACER2 has the cytosolic C terminus and luminal N terminus, which are essential for its activity, correct cellular localization, and regulation for protein glycosylation.